Pendidikan IMPLEMENTATION OF RELIGIOUS EXTRACURRICULAR ACTIVITIES TO DEVELOP STUDENTS' SKILLS AT MTS AL- JAMIYATUL WASLIYAH TEMBUNG - Nur Lala Qomariah.S; Desi Fitriyanti Pane; Khofifah Rizkina Asyraf Hasibuan (Cendekia Madani Nusantara, 2024)
It is hoped that this exploration will provide an explanation of the background to the implementation of strict extracurriculars to grow students' Islamic abilities at MTs Al-Jamiyatul Wasliyah Tembung, how to implement strict extracurriculars to grow students' Islamic abilities at MTs Al-Jamiyatul Wasliyah Tembung, and their impact. regarding strict extracurricular Islamic abilities of students at MTs Al-Jamiyatul Wasliyah Tembung, supporting and suppressing variables for extracurricular strict Islamic abilities of students at MTs Al-Jamiyatul Wasliyah Tembung. This exploration includes a clear subjective examination and the type of exploration is contextual analysis using information gathering procedures, namely: free guided interviews, member perceptions (participatory) and documentation. Meanwhile, the information inspection strategy uses graphic investigation techniques, which include: information reduction investigation, information display, and confirmation. The consequences of this exploration show that: The reason for strict extracurricular activities is that there is no division of learning time in the field of religion. The implementation of strict extracurricular exercise is carried out simultaneously, especially on Saturdays from 3 to 4, including: extracurricular implementation of hadrah, extracurricular implementation of qiraah, implementation of extracurricular recitation of the yellow book, implementation of extracurricular tartil, implementation of extracurricular calligraphy. Strict extracurricular branches include: Hadrah: talented students playing hadrah and shalawat music, Qira'ah: Reading the yellow book: Talented students read qiraah very well. polite student behavior, Tartil: students who are good at reading the Koran according to the rules of recitation, Calligraphy: students who are talented in calligraphy drawing lessons. Supporting and inhibiting factors for strict extracurriculars include: Supporting variables for strict extracurriculars are that the place is spacious and the hardware is accessible. while the inhibiting factor is the absence of equipment, the extracurricular supporting element of qiraah is the place, the members are students who already have basic skills in qiraah, while the inhibiting variable is the students' indifference and enthusiasm, the extracurricular supporting component of recitation of the yellow book of students is not difficult to supervise and is an advantage large number of students while the oppressive element is insufficient time allocation, the supporting variable for extracurricular tartil is the place and school that disciplines students to immediately enter learning tartil while the inhibiting factor is the number of students being too many and not enough time, the supporting variable for extracurricular calligraphy is students who are very energetic and serious during education and the obstacle is the portion.